The intercept : a Jeremy Fisk novel - Wolf, Dick (Wolf, Dick. Jeremy Fisk novel., 2013)
"An adrenaline-fueled thriller debut in the tradition of Three Days of the Condor from the famed creator of TV's Law & Order, featuring NYPD Special Agent Jeremy Fisk, who is New York City's last hope against an ingenious, multi-pronged terrorist attack"--